Preparation method and application of UiO-66-NH2-HSO3 / chitosan composite material

By forming the UiO-66-NH2-HSO3/chitosan composite material on the Zr-based metal organic framework, the hydrogen bond network of acid-base groups and chitosan is used to solve the problem of insufficient proton conduction performance in the prior art. It realizes efficient proton conduction and environmentally friendly preparation process.

CN119119595APending Publication Date: 2024-12-13TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311628721.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-01
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The proton conduction performance of existing proton exchange membrane fuel cells is insufficient, especially the hydrogen bond of UiO-66-NH2-HSO3 materials is limited to within the molecule, the proton transport performance is limited, and the preparation process is not environmentally friendly.

Method used

Using the preparation method of UiO-66-NH2-HSO3/chitosan composite material, the acid-base group-NH2/-HSO3 is simultaneously added to the Zr-based metal organic frame by hydrothermal method to form a complex hydrogen bond network and combine it with The long-chain structure of chitosan forms a higher density hydrogen bond network to improve proton conduction capabilities.

Benefits of technology

It significantly improves the proton conduction ability, improves water stability and mechanical tensile performance, reduces costs, and has simple process, environmentally friendly, and has great industrial utilization value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119595A_ABST
    Figure CN119119595A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a UiO-66-NH2-HSO3 / chitosan composite material, which comprises the following steps: simultaneously loading acid-base groups-NH2 / -HSO3 on a Zr-based metal-organic framework material by using a hydrothermal method to prepare a UiO-66-NH2-HSO3 framework material; and compounding the framework material with chitosan to obtain the UiO-66-NH2-HSO3 / chitosan composite material. The UiO-66-NH2-HSO3 / chitosan composite material disclosed by the invention can be used for a proton exchange membrane fuel cell, chitosan and UiO-66-NH2-HSO3 are compounded, so that the membrane material has relatively good water stability and mechanical tensile property, the chitosan has a long-chain structure,-NH2 is spread over the surface of the chitosan, a hydrogen bond network with higher density and more complex is formed in the whole membrane, and the performance of the membrane is improved. The acid-base pair effect is promoted, so that higher proton conduction performance is realized. Compared with other proton conductive materials, the UiO-66 series MOF disclosed by the invention is relatively mature, and the chitosan is relatively low in cost, so that the UiO-66 series MOF has a relatively good industrial utilization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane materials, and specifically relates to a preparation method and application of a UiO-66-NH2-HSO3 / chitosan composite material. Background Art

[0002] Fuel cells are clean and efficient electrochemical devices that can directly convert chemical energy into electrical energy. Especially now that energy is becoming increasingly scarce, the development of fuel cell technology is very important. Metal-Organic Frameworks (MOFs) are organic-inorganic hybrid materials with intramolecular pores formed by self-assembly of organic ligands and metal ions or clusters through coordination bonds. Applying them to the proton exchange membrane of proton exchange membrane fuel cells can effectively improve the proton exchange capacity. The proton exchange membranes currently on the market generally use perfluorosulfonic acid membranes, but their cost is high and the preparation process is not environmentally friendly.

[0003] UiO series MOFs have advantages such as excellent water stability, easy modification and mature synthesis technology. In particular, UiO-66-NH2 and UiO-66-HSO3 have been shown to have good proton conductivity. There are generally two mechanisms for the conduction of protons in proton membranes: proton hopping mechanism (Grotthuss mechanism) and proton transport mechanism (Vehicle mechanism), which are respectively achieved by the protonation and deprotonation of molecules to achieve hopping on the hydrogen bond network and by the self-diffusion transport of proton carriers. When the acid-base pair groups -NH2 and -HSO3 exist in the system at the same time, an additional hydrogen bond network can be formed between the acid-base pairs, promoting the Grotthuss mechanism and thus improving the proton conductivity, but the specific mechanism of action is still unclear; and according to the Grotthuss mechanism, the proton transport in fuel cells under high humidity mainly depends on the proton jumping on the hydrogen bond network to achieve efficient transport. The acid-base pair effect of the -NH2 / -HSO3 groups can increase the density of the hydrogen bond network, but the hydrogen bonds of pure UiO-66-NH2-HSO3 are limited to the molecule, and the effect of improving the proton transport performance is limited. Therefore, combining it with other materials becomes a modification direction. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a UiO-66-NH2-HSO3 / chitosan composite material in view of the deficiencies of the above-mentioned prior art. The method comprises the following steps: simultaneously loading the acid-base groups -NH2 / -HSO3 on a Zr-based metal-organic framework material to form a UiO-66-NH2-HSO3 framework material, and then compounding the framework material with chitosan to form a UiO-66-NH2-HSO3 / chitosan composite material for use in proton exchange membrane fuel cells. By controlling the strategy of the acid-base pair ratio, the proton conduction mechanism is deeply studied to improve the performance of the proton exchange membrane.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a UiO-66-NH2-HSO3 / chitosan composite material, the method comprising the following steps:

[0006] S1. Preparation of UiO-66-NH2-HSO3 precursor solution

[0007] Dissolving monosodium 2-sulfonate terephthalate and 2-aminoterephthalic acid in N,N-dimethylacetamide and formic acid, performing ultrasonic treatment, adding zirconium oxychloride octahydrate, and continuing ultrasonic treatment to obtain a UiO-66-NH2-HSO3 precursor solution;

[0008] Preparation of S2 and UiO-66-NH2-HSO3 framework materials

[0009] The UiO-66-NH2-HSO3 precursor solution obtained in S1 was subjected to a hydrothermal reaction. After the reaction was completed, the product was separated by centrifugation. The obtained precipitate was washed with N,N-dimethylacetamide and acetone for three times, centrifuged, and then vacuum dried to obtain a UiO-66-NH2-HSO3 framework material.

[0010] Preparation of S3, UiO-66-NH2-HSO3 / chitosan composites

[0011] The UiO-66-NH2-HSO3 framework material obtained by S2 is mixed with pure water and stirred evenly; then chitosan is added and ultrasonic treatment is performed; acetic acid is added, stirred evenly and placed in a vacuum drying oven to remove bubbles, until the mixed liquid is uniform and free of bubbles, poured into a square culture dish, and dried to obtain a UiO-66-NH2-HSO3 / chitosan composite material.

[0012] Preferably, the usage ratio of monosodium 2-sulfonate terephthalate, 2-aminoterephthalic acid, N,N-dimethylacetamide and formic acid in S1 is 3-30 mmol:30-3 mmol:30 mL:31 mmol; and the molar ratio of zirconium oxychloride octahydrate to formic acid is 1:1.

[0013] Preferably, the frequencies of the two ultrasonic treatments in S1 are both 20-40 KHz, and the duration is 30-60 min.

[0014] Preferably, the temperature of the hydrothermal reaction in S2 is 120-180° C. and the time is 12-24 h.

[0015] Preferably, the centrifugal speed in S2 is 8000-10000 rpm, and the time is 7-15 min. Preferably, the vacuum drying temperature in S2 is 70-90° C., and the time is 8-12 h.

[0016] Preferably, the usage ratio of the UiO-66-NH2-HSO3 framework material, chitosan, pure water and acetic acid in S3 is 0.2-0.6 g: 2 g: 50 mL: 1-2.5 mL.

[0017] Preferably, the stirring time in S3 is 1 to 2 hours; the ultrasonic frequency is 20 to 40 kHz, and the time is 15 to 40 minutes.

[0018] Preferably, the drying temperature in S3 is 70-90° C. and the drying time is 8-12 hours.

[0019] The present invention also provides an application of the UiO-66-NH2-HSO3 / chitosan composite material, and the UiO-66-NH2-HSO3 / chitosan composite material is used for a proton exchange membrane fuel cell.

[0020] Compared with the prior art, the present invention has the following outstanding effects:

[0021] 1. The present invention provides a method for preparing a UiO-66-NH2-HSO3 / chitosan composite material, wherein the acid-base groups -NH2 / -HSO3 are simultaneously added to the Zr-based metal organic framework UiO-66 by a hydrothermal method to form an acid-base pair within the molecule, thereby forming a complex hydrogen bond network, forming a proton donor-acceptor channel between the acid and the base, which serves as an additional proton transmission channel, promotes the Grotthuss mechanism in the proton conduction mechanism, and can effectively improve the proton conduction capacity.

[0022] 2. The hydrogen bonds of pure UiO-66-NH2-HSO3 materials are confined to the molecules, and the effect of improving the proton transport performance is limited; chitosan has a long-chain structure and -NH2 is distributed all over the surface, which can form a higher density and more complex hydrogen bond network in the entire membrane, promote the acid-base effect, and thus achieve higher proton conduction performance; in addition, the combination of chitosan and UiO-66-NH2-HSO3 also enables the membrane material to obtain better water stability and mechanical tensile properties.

[0023] 3. Compared with other proton conductive materials, the UiO-66 series MOF in the present invention is relatively mature, and the cost of chitosan is relatively low. The prepared UiO-66-NH2-HSO3 / chitosan composite material has high proton conductivity, simple synthesis process, environmental friendliness, and great industrial utilization value and environmental value.

[0024] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a scanning electron microscope image of the UiO-66-NH2-HSO3 framework material in Example 1 of the present invention.

[0026] Figure 2 This is a scanning electron microscope image of the UiO-66-NH2-HSO3 / chitosan composite material in Example 1 of the present invention.

[0027] Figure 3 3 is the XRD diagram of the UiO-66-NH2-HSO3 framework material with different acid-base group ratios in Examples 1 to 5 of the present invention.

[0028] Figure 4 The UiO-66-NH2-HSO3 framework material with different acid-base group ratios in Examples 1 to 5 of the present invention is 1 HNMR spectrum.

[0029] Figure 5 This is the AC impedance diagram of the UiO-66-NH2-HSO3 framework material at 95% RH in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] Example 1

[0031] This embodiment is a method for preparing a UiO-66-NH2-HSO3 / chitosan composite material, which comprises the following steps:

[0032] S1. Preparation of UiO-66-NH2-HSO3 precursor solution

[0033] 15 mmol of monosodium 2-sulfonate terephthalate and 15 mmol of 2-aminoterephthalic acid were dissolved in 30 mL of N, N-dimethylacetamide and 31 mmol of formic acid, and ultrasonic treatment was performed for 30 min at a frequency of 40 KHz; 31 mmol of zirconium oxychloride octahydrate was then added, and ultrasonic treatment was continued for 60 min at a frequency of 20 KHz to obtain a UiO-66-NH2-HSO3 precursor solution;

[0034] Preparation of S2 and UiO-66-NH2-HSO3 framework materials

[0035] The UiO-66-NH2-HSO3 precursor solution obtained in S1 was subjected to a hydrothermal reaction at a temperature of 150°C for 24 hours. After the reaction was completed, the product was separated by centrifugation at a speed of 10000 rpm for 10 minutes. The precipitate was washed with N, N-dimethylacetamide and acetone for 3 times, centrifuged, and then dried in a vacuum oven at 80°C for 8 hours to obtain a UiO-66-NH2-HSO3 framework material named UiO-66-NH2-HSO3-1:1.

[0036] Preparation of S3, UiO-66-NH2-HSO3 / chitosan composites

[0037] Take 0.4g S2 to obtain the UiO-66-NH2-HSO3 framework material, mix it with 50mL pure water, and stir it for 1h; then add 2g chitosan, ultrasonically treat it for 30min at a frequency of 30KHz; then add 2mL acetic acid, stir it for 2h, place it in a vacuum drying oven to remove bubbles, until the mixed liquid is uniform and free of bubbles, pour it into a square culture dish, and dry it at 70℃ for 8h to obtain the UiO-66-NH2-HSO3 / chitosan composite material.

[0038] Figure 1 is a scanning electron microscope image of the UiO-66-NH2-HSO3 framework material synthesized in this embodiment. Figure 1 It can be seen intuitively that a typical octahedral crystal configuration of UiO-66-NH2-HSO3 was obtained, which is consistent with the reported UiO-66 series MOF structure, indicating that the crystal has been successfully grown.

[0039] Figure 2 This is a scanning electron microscope image of the UiO-66-NH2-HSO3 / chitosan composite material prepared in this embodiment. From the figure, it can be seen that the composite film is relatively flat as a whole, has good membrane surface characteristics, and has small protrusions evenly dispersed locally. This is the UiO-66-NH2-HSO3 material doped therein, proving that the UiO-66-NH2-HSO3 / chitosan composite material has been successfully compounded.

[0040] Example 2

[0041] In order to explore the mechanism of action of different proportions of acid-base pairs on proton conductivity, the UiO-66-NH2-HSO3 framework material was prepared in this example. The method was the same as steps S1 and S2 in Example 1, except that the amount of 2-sulfonato monosodium terephthalate was 25 mmol, and the amount of 2-aminoterephthalic acid was 5 mmol. The final framework material was named UiO-66-NH2-HSO3-1:5.

[0042] Example 3

[0043] In this embodiment, UiO-66-NH2-HSO3 framework material was prepared. The preparation method was the same as steps S1 and S2 in Example 1, except that the amount of 2-sulfonato monosodium terephthalate was 5 mmol, the amount of 2-aminoterephthalic acid was 25 mmol, and the final framework material was named UiO-66-NH2-HSO3-5:1.

[0044] Example 4

[0045] In this embodiment, UiO-66-NH2-HSO3 framework material was prepared. The preparation method was the same as steps S1 and S2 in Example 1, except that the amount of 2-sulfonato monosodium terephthalate was 3 mmol, the amount of 2-aminoterephthalic acid was 30 mmol, and the final framework material was named UiO-66-NH2-HSO3-10:1.

[0046] Example 5

[0047] In this embodiment, UiO-66-NH2-HSO3 framework material was prepared. The preparation method was the same as steps S1 and S2 in Example 1, except that the amount of 2-sulfonato monosodium terephthalate was 30 mmol, the amount of 2-aminoterephthalic acid was 3 mmol, and the final framework material was named UiO-66-NH2-HSO3-1:10.

[0048] The structure and performance tests of the UiO-66-NH2-HSO3 framework materials with different acid-base group ratios prepared in Examples 1 to 5 were carried out, and the results are as follows:

[0049] Figure 3 It is the XRD pattern of UiO-66-NH2-HSO3 framework materials with different acid-base group ratios prepared in Examples 1 to 5. It can be seen from the figure that there is no obvious difference in the XRD measured for UiO-66-NH2-HSO3 framework materials with different acid-base group ratios, indicating that different ratios of groups do not affect the peak position and have little effect on the structure of the framework material.

[0050] Figure 4 The UiO-66-NH2-HSO3 framework material with different acid-base group ratios prepared in Examples 1 to 5 1HNMR test results, after analysis and calculation of the test results, it was found that the -NH2 / -HSO3 ratio in the framework material was consistent with the feed ratio, that is, the expected UiO-66-NH2-HSO3-1:1, UiO-66-NH2-HSO3-1:5, UiO-66-NH2-HSO3-5:1, UiO-66-NH2-HSO3-10:1 and UiO-66-NH2-HSO3-1:10 were successfully synthesized.

[0051] The test method for proton conductivity is as follows: weigh 30 mg of UiO-66-NH2-HSO3 framework material, place it in a round stainless steel mold, keep it under a pressure of 4 tons for 30 seconds, press it into a disc with a diameter of 8 mm and a thickness of 1.8-2.2 mm, clamp it with a steel plate, put it in a high and low temperature alternating box, adjust the ambient humidity, perform AC impedance test through an electrochemical workstation, and calculate the activation energy by fitting the curve of impedance values ​​at different temperatures.

[0052] The proton conductivity of UiO-66-NH2-HSO3 framework materials with different acid-base group ratios is shown in Table 1. The proton conductivity gradually increases with the increase of relative humidity, indicating that the UiO-66-NH2-HSO framework material can enhance the Grotthuss mechanism of proton transport under high humidity, greatly improving the proton conductivity of the material.

[0053] Table 1 Proton conductivity of UiO-66-NH2-HSO3 framework material

[0054]

[0055] Figure 5 This is a graph showing the AC impedance test results of the framework material UiO-66-NH2-HSO3-1:1 of Example 1 at 95% RH.

[0056] The UiO-66-NH2-HSO3 framework materials synthesized in Examples 1 to 5 of the present invention were subjected to an AC impedance test at 95% RH. It was found that the proton conductivity of UiO-66-NH2-HSO3-1:1 in Example 1 reached 1.16×10 -3 S / cm, the activation energy reaches 0.61eV; the proton conductivity of UiO-66-NH2-HSO3-1:5 in Example 2 reaches 6.33×10 -3 S / cm, the activation energy reaches 0.89 eV; the proton conductivity of UiO-66-NH2-HSO3-5:1 in Example 3 reaches 5.36×10 -4 S / cm, the activation energy reaches 1.064eV; the proton conductivity of UiO-66-NH2-HSO3-10:1 in Example 4 reaches 5.34×10 -4S / cm, the activation energy reaches 0.98eV; the proton conductivity of UiO-66-NH2-HSO3-1:10 in Example 5 reaches 3.45×10 -3 , the activation energy reaches 1.1eV. It is proved that when different proportions of ligands containing -NH2 and -HSO3 are added to the Zr-based metal organic framework UiO-66, there are acid-base pairs in the system at the same time, which can form an additional hydrogen bond network between the acid-base pairs, forming a proton donor-acceptor channel between the acid and the base, promoting the Grotthuss mechanism, and thus improving the proton conduction ability. When the molar ratio of the acid-base groups -NH2 and -HSO3 is 1:5, the proton conduction ability is the strongest. This may be because the hydrophilicity of the -NH2 / -HSO3 acid-base groups is different, and the acid-base effect will have an excitation process when facing humidity, that is, when the humidity reaches a certain level, the acid-base effect is excited, and if the humidity is insufficient, the acid-base effect is inhibited. In addition, since the hydrophilicity of -HSO3 is much greater than that of -NH2, at the same humidity, UiO-66 with more -HSO3 groups shows higher hydrophilicity, thereby forming more hydrogen bonds and obtaining higher proton conduction performance.

[0057] The proton conductivity of the UiO-66-NH2-HSO3 / chitosan composite material prepared by using the framework material UiO-66-NH2-HSO3-1:1 of Example 1 reached 8.8×10 -2 S / cm, and the activation energy is 0.82eV, indicating that the proton conductivity and activation energy are improved by combining it with chitosan. The increase in activation energy shows that the proton conduction mechanism is more dependent on the Grotthuss mechanism. The -NH2 group is a group that easily forms hydrogen bonds. The large amount of -NH2 on chitosan makes it possible to form a high-density complex hydrogen bond network in the material.

[0058] Example 6

[0059] This embodiment is a method for preparing a UiO-66-NH2-HSO3 / chitosan composite material, which comprises the following steps:

[0060] S1. Preparation of UiO-66-NH2-HSO3 precursor solution

[0061] 15 mmol of monosodium 2-sulfonate terephthalate and 15 mmol of 2-aminoterephthalic acid were dissolved in 30 mL of N, N-dimethylacetamide and 31 mmol of formic acid, and ultrasonic treatment was performed for 40 min at a frequency of 40 KHz; 31 mmol of zirconium oxychloride octahydrate was then added, and ultrasonic treatment was continued for 50 min at a frequency of 30 KHz to obtain a UiO-66-NH2-HSO3 precursor solution;

[0062] Preparation of S2 and UiO-66-NH2-HSO3 framework materials

[0063] The UiO-66-NH2-HSO3 precursor solution obtained in S1 was subjected to a hydrothermal reaction at a temperature of 120°C for 12 hours. After the reaction was completed, the product was separated by centrifugation at a speed of 8000 rpm for 7 minutes. The obtained precipitate was washed with N,N-dimethylacetamide and acetone for 3 times, centrifuged, and then dried in a vacuum oven at 70°C for 8 hours to obtain a UiO-66-NH2-HSO3 framework material.

[0064] Preparation of S3, UiO-66-NH2-HSO3 / chitosan composites

[0065] Take 0.4g S2 to obtain the UiO-66-NH2-HSO3 framework material, mix it with 50mL pure water, and stir for 2h; then add 2g chitosan, ultrasonically treat for 40min at a frequency of 20KHz; then add 1.5mL acetic acid, stir for 1h, place it in a vacuum drying oven to remove bubbles, until the mixture is uniform and free of bubbles, pour it into a square culture dish, and dry it at 70℃ for 8h to obtain the UiO-66-NH2-HSO3 / chitosan composite material.

[0066] The proton conductivity of the UiO-66-NH2-HSO3 / chitosan composite material obtained in this example is 9.3×10 -2 S / cm, and the activation energy is 0.93 eV.

[0067] Example 7

[0068] This embodiment is a method for preparing a UiO-66-NH2-HSO3 / chitosan composite material, which comprises the following steps:

[0069] S1. Preparation of UiO-66-NH2-HSO3 precursor solution

[0070] 15 mmol of monosodium 2-sulfonate terephthalate and 15 mmol of 2-aminoterephthalic acid were dissolved in 30 mL of N, N-dimethylacetamide and 31 mmol of formic acid, and ultrasonic treatment was performed for 60 min at a frequency of 20 KHz; 31 mmol of zirconium oxychloride octahydrate was then added, and ultrasonic treatment was continued for 40 min at a frequency of 40 KHz to obtain a UiO-66-NH2-HSO3 precursor solution;

[0071] Preparation of S2 and UiO-66-NH2-HSO3 framework materials

[0072] The UiO-66-NH2-HSO3 precursor solution obtained in S1 was subjected to a hydrothermal reaction at a temperature of 150°C for 18 hours. After the reaction was completed, the product was separated by centrifugation at a speed of 9000 rpm for 11 minutes. The precipitate was washed with N,N-dimethylacetamide and acetone for three times, centrifuged, and then dried in a vacuum oven at 80°C for 10 hours to obtain a UiO-66-NH2-HSO3 framework material.

[0073] Preparation of S3, UiO-66-NH2-HSO3 / chitosan composites

[0074] Take 0.6g of S2 to obtain the UiO-66-NH2-HSO3 framework material, mix it with 50mL of pure water, and stir it for 1.5h; then add 2g of chitosan, ultrasonically treat it for 15min at a frequency of 40KHz; then add 1mL of acetic acid, stir it for 1.5h, place it in a vacuum drying oven to remove bubbles, until the mixed liquid is uniform and free of bubbles, pour it into a square culture dish, and dry it at 80℃ for 10h to obtain the UiO-66-NH2-HSO3 / chitosan composite material.

[0075] The proton conductivity of the UiO-66-NH2-HSO3 / chitosan composite material obtained in this example is 6.4×10 -2 S / cm, and the activation energy is 0.73 eV.

[0076] Example 8

[0077] This embodiment is a method for preparing a UiO-66-NH2-HSO3 / chitosan composite material, which comprises the following steps:

[0078] S1. Preparation of UiO-66-NH2-HSO3 precursor solution

[0079] 15 mmol of monosodium 2-sulfonate terephthalate and 15 mmol of 2-aminoterephthalic acid were dissolved in 30 mL of N, N-dimethylacetamide and 31 mmol of formic acid, and ultrasonic treatment was performed for 60 min at a frequency of 25 KHz; 31 mmol of zirconium oxychloride octahydrate was then added, and ultrasonic treatment was continued for 30 min at a frequency of 40 KHz to obtain a UiO-66-NH2-HSO3 precursor solution;

[0080] Preparation of S2 and UiO-66-NH2-HSO3 framework materials

[0081] The UiO-66-NH2-HSO3 precursor solution obtained in S1 was subjected to a hydrothermal reaction at a temperature of 180°C for 24 hours. After the reaction was completed, the product was separated by centrifugation at a speed of 10,000 rpm for 15 minutes. The precipitate was washed with N,N-dimethylacetamide and acetone for three times, centrifuged, and then dried in a vacuum oven at 90°C for 12 hours to obtain a UiO-66-NH2-HSO3 framework material.

[0082] Preparation of S3, UiO-66-NH2-HSO3 / chitosan composites

[0083] Take 0.2g of S2 to obtain the UiO-66-NH2-HSO3 framework material, mix it with 50mL of pure water, and stir it for 1h; then add 2g of chitosan, ultrasonically treat it for 30min at a frequency of 30KHz; then add 2.5mL of acetic acid, stir it for 2h, place it in a vacuum drying oven to remove bubbles, until the mixed liquid is uniform and free of bubbles, pour it into a square culture dish, and dry it at 90℃ for 12h to obtain the UiO-66-NH2-HSO3 / chitosan composite material.

[0084] The proton conductivity of the UiO-66-NH2-HSO3 / chitosan composite material obtained in this example is 0.1 S / cm, and the activation energy is 0.97 eV.

[0085] The results of Example 1 and Examples 6 to 8 show that ultrasonic dispersion treatment and sufficient solvent can further ensure that the solute is fully dispersed in the solvent, so that the final material performance is optimal. In the present invention, the optimal ratio of 2-sulfonato terephthalic acid monosodium, 2-aminoterephthalic acid and N, N-dimethylacetamide is 15mmol:15mmol:30mL; the optimal molar ratio of zirconium oxychloride octahydrate and formic acid is 1:1. In the preparation process of UiO-66-NH2-HSO3 / chitosan composite material, pure water and acetic acid form acetic acid solution for dissolving chitosan, and chitosan is best soluble only in acetic acid at a specific concentration. In the present invention, the best effect is achieved when the ratio of pure water to acetic acid is 50mL:2mL. In addition, when the UiO-66-NH2-HSO3 framework material is compounded with chitosan, too little UiO-66-NH2-HSO3 framework material cannot exert its effect, while too much will increase the brittleness of the membrane and reduce the mechanical properties of the proton exchange membrane. Therefore, the best effect is achieved when the ratio of UiO-66-NH2-HSO3 framework material to chitosan is 0.4g:2g.

[0086] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a UiO-66-NH2-HSO3 / chitosan composite material, characterized in that: The method comprises the following steps: S1. Preparation of UiO-66-NH2-HSO3 precursor solution Dissolving monosodium 2-sulfonate terephthalate and 2-aminoterephthalic acid in N,N-dimethylacetamide and formic acid, performing ultrasonic treatment, adding zirconium oxychloride octahydrate, and continuing ultrasonic treatment to obtain a UiO-66-NH2-HSO3 precursor solution; Preparation of S2 and UiO-66-NH2-HSO3 framework materials The UiO-66-NH2-HSO3 precursor solution obtained in S1 was subjected to a hydrothermal reaction. After the reaction was completed, the product was separated by centrifugation. The obtained precipitate was washed with N,N-dimethylacetamide and acetone for three times, centrifuged, and then vacuum dried to obtain a UiO-66-NH2-HSO3 framework material. Preparation of S3, UiO-66-NH2-HSO3 / chitosan composites The UiO-66-NH2-HSO3 framework material obtained by S2 is mixed with pure water and stirred evenly; then chitosan is added and ultrasonic treatment is performed; acetic acid is added, stirred evenly and placed in a vacuum drying oven to remove bubbles, until the mixed liquid is uniform and free of bubbles, poured into a square culture dish, and dried to obtain a UiO-66-NH2-HSO3 / chitosan composite material.

2. The method for preparing a UiO-66-NH2-HSO3 / chitosan composite material according to claim 1, characterized in that: The usage ratio of the monosodium 2-sulfonate terephthalate, 2-aminoterephthalic acid, N,N-dimethylacetamide and formic acid in S1 is 3-30 mmol: 30-3 mmol: 30 mL: 31 mmol; the molar ratio of the zirconium oxychloride octahydrate to formic acid is 1:

1.

3. The method for preparing a UiO-66-NH2-HSO3 / chitosan composite material according to claim 1, characterized in that: The frequencies of the two ultrasonic treatments in S1 are both 20-40 KHz, and the duration is 30-60 min.

4. The method for preparing a UiO-66-NH2-HSO3 / chitosan composite material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in S2 is 120-180°C and the time is 12-24h.

5. The method for preparing a UiO-66-NH2-HSO3 / chitosan composite material according to claim 1, characterized in that: The centrifugal speed in S2 is 8000-10000 rpm, and the time is 7-15 min.

6. The method for preparing a UiO-66-NH2-HSO3 / chitosan composite material according to claim 1, characterized in that: The vacuum drying in step S2 is carried out at a temperature of 70 to 90° C. and for a time of 8 to 12 hours.

7. The method for preparing a UiO-66-NH2-HSO3 / chitosan composite material according to claim 1, characterized in that: The usage ratio of the UiO-66-NH2-HSO3 framework material, chitosan, pure water and acetic acid described in S3 is 0.2-0.6 g: 2 g: 50 mL: 1-2.5 mL.

8. The method for preparing a UiO-66-NH2-HSO3 / chitosan composite material according to claim 1, characterized in that: The stirring time in S3 is 1 to 2 hours; the ultrasonic frequency is 20 to 40 KHz, and the time is 15 to 40 minutes.

9. The method for preparing a UiO-66-NH2-HSO3 / chitosan composite material according to claim 1, characterized in that: The drying temperature in S3 is 70-90° C. and the drying time is 8-12 hours.

10. An application of the UiO-66-NH2-HSO3 / chitosan composite material obtained according to the preparation method of claims 1 to 9, characterized in that: The UiO-66-NH2-HSO3 / chitosan composite material is used for proton exchange membrane fuel cells.